Comprehensive Identification of Tumor-associated Antigens via Isolation of Human Monoclonal Antibodies that may be Therapeutic - Kurosawa, Yoshikazu (The Korean Association of Immunobiologists, 2009)
Although the success of trastuzumab and rituximab for treatment of breast cancer and non-Hodgkins lymphoma, respectively, suggests that monoclonal antibodies (mAbs) will become important therapeutic agents against a wider range of cancers, useful therapeutic Abs are not yet available for the majority of the human cancers because of our lack of knowledge of which antigens (Ags) are likely to become useful targets. We established a procedure for comprehensive identification of such Ags through the extensive isolation of human mAbs that may be therapeutic. Using the phage-display Ab library we isolated a large number of human mAbs that bind to the surface of tumor cells. They were individually screened by immunostaining, and clones that preferentially and strongly stained the malignant cells were chosen. The Ags recognized by those clones were isolated by immunoprecipitation and identified by mass spectrometry (MS). We isolated 2,114 mAbs with unique sequences and identified 25 distinct Ags highly expressed on several carcinomas. Of those 2,114 mAbs 434 bound to specifically to one of the 25 Ags. I am going to discuss how we could select proper target Ags for therapeutic Abs and candidate clones as therapeutic agents.